Urbanization and the Rising Burden of Diabetes Mellitus through an Epidemiological Analysis of Urban Population Risk Factors - Nguyễn Ngọc Mai Thảo; Huy-Thanh Nguyen; Quang Cuong Tran (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
This research investigated how diabetes spreads and what triggers it within Vietnam’s urban centers. Our team used a quantitative cross-sectional design to get a clear epidemiological snapshot. Between January and April 2025, the gathered data from 1,250 residents across Hanoi, Ho Chi Minh City, and Da Nang. A direct measurement of BMI, waist-to-hip ratios, and fasting blood glucose, while also using questionnaires to track participant lifestyles. To round out the analysis, we pulled secondary figures from WHO databases and national health reports. The results are concerning. By 2025, diabetes prevalence in these cities hit 7.2%, but prediabetes is the bigger story, affecting 14.8% of the population. Geographically, Ho Chi Minh City leads with an 8.2% rate, followed by Hanoi at 6.9% and Da Nang at 6.0%. When looking at why these numbers are climbing, obesity (OR 3.45) and sedentary habits (OR 2.80) stand out as the primary culprits, alongside hypertension and genetics. It is clear that Vietnam’s rapid shift to urban living is driving this metabolic crisis. Moving forward, we need deeper research into how long-term city environments and changing diets specifically accelerate this disease.